PENGANGKUTAN BBM BERSUBSIDI DITINJAU DARI UNDANGAN UNDANGAN REPUBLIK INDONESIA NOMOR 22 TAHUN 2001 TENTANG MIGAS - Erfandi Erfandi; Abshoril Fithry; Rusfandi Rusfandi (Fakultas Hukum Universitas Wiraraja, 2025)
Transportation of subsidized fuel oil (BBM) is a crucial element in the distribution of national energy that aims to provide affordable energy for the community. However, the Law of the Republic of Indonesia No. 22 of 2001 concerning Oil and Gas (Uu Migas) only regulates the transportation of fuel from upstream to downstream through the pipeline, without including the distribution of the Public Fuel Filling Station (SPBU) to small businesses and end consumers. The vacancy of this norm raises a vulnerable legal gap of being misused, inhibiting the achievement of subsidized fuel distribution that is on target. This study aims to examine the legal regulation of subsidized fuel transportation from gas stations to final consumers according to the Oil and Gas Law and assess the implementation of law enforcement in the field. The method used is a normative juridical approach with qualitative analysis of legislation, legal doctrine, and secondary legal material. The results showed that the Oil and Gas Law has not provided a clear regulation on the last transportation stage of subsidized BBM, which has an impact on the weakness of supervision and the rise of distribution deviations. Also found involvement of unscrupulous officials in illegal practices that aggravate the situation. Thus, more comprehensive regulation updates are needed and consistent law enforcement so that subsidized fuel distribution can run fairly, transparently, and in accordance with national energy policy objectives.